Dynamics of Fatty Acids, Tocopherols and Phenolic Compounds Biogenesis During Olive (Olea europaea L.) Fruit Ontogeny. (6th August 2016) - Bodoira, Romina; Torres, Mariela; Pierantozzi, Pierluigi; Aguate, Fernando; Taticchi, Agnese; Servili, Maurizio; Maestri, Damián
Abstract: Fatty acids, tocopherols, and phenolic compounds biogenesis from two major Spanish olive cultivars (Arbequina and Manzanilla) were analyzed for the function of the thermal regime during the fruit ontogeny in a non‐Mediterranean environment. Bilinear models characterized the dynamics of fatty acid biogenesis. Regressions between the accumulated thermal time (TT) and the levels of both oleic and linoleic acids showed different responses to temperature of each olive cultivar. After reaching similar absolute maximum oleic acid contents at similar TT, the levels of this fatty acid decreased markedly in cv. Arbequina and its final concentration was 10 % lower than that found in cv. Manzanilla. In both cultivars, concentrations of all tocopherol isoforms were negatively associated with the TT accumulated over the entire oil accumulation period. Dynamics of phenolic compounds biogenesis showed no clear tendencies with TT. Nevertheless, and whatever the stage of fruit development, secoiridoids were the major phenolic components. Results suggest greater sensitivity of fatty acid metabolism to temperature in cv. Arbequina. This fact points out the necessity of appropriate evaluation of the ambient thermal characteristics before introducing this cultivar into new growing environments.